Prediksi Pertumbuhan Jumlah UMKM di Jawa Barat Menuju Indonesia Emas 2045 Menggunakan Regresi Linear - Issa Wirakusumah, Raden Mochamad; Hesananda, Rizki (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
This research delves into the projection of the number of Micro, Small, and Medium Enterprises (MSMEs) in West Java, employing the methodology of linear regression. The study utilizes open data from West Java to analyze factors influencing MSME growth, such as government support, infrastructure, financial access, and demographic characteristics. The regression model is formulated, trained, and optimized to project MSME growth up to the year 2045, aligning with the vision of Indonesia Emas. The results reveal a significant upward trend in MSME numbers, particularly evident in regions like Bogor, under the auspices of West Java. The collaborative efforts of provincial and local governments, supported by effective policies, contribute to the optimistic projections. The study's findings underscore the pivotal role of sustained collaboration and adaptive policies in fostering a conducive environment for MSMEs. As Indonesia strives for economic growth and inclusivity, understanding the dynamics of MSMEs becomes instrumental. This research aims to guide policymakers in formulating strategic interventions for the sustainable development of MSMEs, ensuring their central role in the realization of Indonesia Emas by 2045.